(untitled) (Salam International Academic Journal, 2024)
Constitution is the most important legal and legislative document of a country, regulating all affaris, aspects and structures of the state’s system. As a fundamental necessity for human societies, constitutions have already addressed these needs for quite long period, and will continue to play a vital role in fulfilling them, particularly in Afghanistan. This study examines the necessity of a constitution for all countries, with a specific focus on Afghanistan, discussing why a constitution is particularly important for Afghanistan in the present era. We also explore the role that a constitution can play in establishing a robust political system. The research methodology employed is descriptive-analytical, with a qualitative approach based on the type of content and findings. Materials were primarily gathered from library resources, with very limited use of internet sources. This research paper delves into various aspects of the topic, including the definition of a constitution, the historical evolution of constitutions, the position of the constitution in Islamic law, and the need for a constitution in Afghanistan. The study concludes with a brief summary, suggestions, and references.